Hubungan Antara Hasil Pembelajaran Geografi Dengan Mitigasi Terhadap Bencana Banjir SMP Negeri 3 Grogol,Kecamatan Grogol, Kabupaten Sukoharjo - Primordia, Estuarin, Drs. Rubino Rubiyanto, M.Pd (2016)
Sukoharjo regency is one of regencies in Central Java and one of the flood-prone area. In 2012 when the Bengawan Solo river overflowed, six districts in Sukoharjo each Grogol, Mojolaban, Polokarto . This research was conducted in SMP Negeri 3 Grogol that aims to describe the relationship between geography learning outcomes by mitigating against floods in SMP Negeri 3 Grogol, Grogol, Sukoharjo. Sempel taken totaled 103 students. The technique of collecting data using questionnaires, observation and documentation. Requirements analysis is conducted to test the validity and reliability testing. Recent research results show that (1) the level of knowledge of learning geography students in learningevalasi geography class VIII SMP Negeri 3 Grogol categorized as good with a percentage of 89,32%. (2) The level of knowledge of students in flood mitigation in class VIII SMP Negeri 3 Grogol categorized very well with a percentage of 82.84%. (3) The relationship between geography learning outcomes by mitigating against floods in the low category with countless r 0,03. Keywords: Knowledge Mitigation, Grade VIII SMP Negeri 3 Grogol, floods